2022
DOI: 10.1021/acs.orglett.2c02275
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Three-Component Cross-Coupling of Conjugated Dienes with Indoles Using Ethynylbenziodazolones as Electrophilic Alkynylating Reagents

Abstract: A palladium-catalyzed regioselective 1,2-alkynyl-carbonalization of conjugated dienes with ethynylbenziodazolone (EBZ) and indoles has been developed for the first time. Various molecules containing alkenyl, alkynyl, and indole groups were readily obtained. Moreover, the resulting products can be applied to various derivatizations. This protocol uses EBZ as an electrophilic alkynylating reagent, avoiding the byproduct of dimerization of alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In our ongoing efforts to develop effective methods for hydrofunctionalization of dienes 10 and transformations of indoles at the C2 position, 11 green, inexpensive and resource-abundant metal catalysts have made good progress in the hydrofunctionalization of olefins in recent years. 12 Then we envisioned whether the hydroarylation of 1,3-dienes with indoles at the C2 position could be achieved by employing inexpensive metal catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…In our ongoing efforts to develop effective methods for hydrofunctionalization of dienes 10 and transformations of indoles at the C2 position, 11 green, inexpensive and resource-abundant metal catalysts have made good progress in the hydrofunctionalization of olefins in recent years. 12 Then we envisioned whether the hydroarylation of 1,3-dienes with indoles at the C2 position could be achieved by employing inexpensive metal catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is urgent to develop effective methods to realize the enantioselective alkynylative difunctionalization of unactivated alkenes. For the alkynylative difunctionalization of conjugated alkenes, there are only two examples [112,113] . The difficulty of alkynylative difunctionalization of conjugated alkenes lies in the control of selectivity, including regioselectivity and enantioselectivity.…”
Section: Discussionmentioning
confidence: 99%
“…For the alkynylative difunctionalization of conjugated alkenes, there are only two examples. [112,113] The difficulty of alkynylative difunctionalization of conjugated alkenes lies in the control of selectivity, including regioselectivity and enantioselectivity.…”
Section: Discussionmentioning
confidence: 99%
“…[114][115][116] Recently, the Chen group reported a palladium-catalyzed three-component cross-coupling of 1,4-dienes with indoles and EBZ reagents (Scheme 29). 117 Interestingly, they showed that this class of reagents outperformed EBX reagents, which produced mixture of 1,2-and 1,4-functionalization products.…”
Section: C(sp 3 )-Csp Bond Formationmentioning
confidence: 99%